Analisis Wacana Kritis Norman Fairclough Pada Pemberitaan Internasionalisasi Bahasa Indonesia Di Media Antaranews.Com - Sari, Wulan Permata; Setyonegoro, Agus; Priyanto, Priyanto (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2025)
This study aims to analyze news coverage regarding the internationalization of the Indonesian language in Antaranews.com. The focus of this research is to identify the representation of the Indonesian language within media discourse and to understand the construction of reality built through the news coverage. This study employs a qualitative approach using Norman Fairclough’s Critical Discourse Analysis (CDA) method. The data in this research consist of four news texts analyzed through Fairclough's three dimensions of CDA: the textual dimension, the discursive practice dimension, and the social practice dimension. Data collection was carried out through documentation techniques, while data validity was ensured through internal validity. Based on the results, it can be concluded that the news coverage of the internationalization of the Indonesian language on Antaranews.com constructs a discourse that emphasizes nationalism and pride in UNESCO’s recognition. In the textual dimension, the news narratives highlight national achievements and cultural diplomacy as the main factors behind UNESCO’s recognition. In the discursive practice dimension, discourse strategies are identified that aim to strengthen the legitimacy of national policies related to the internationalization of the Indonesian language. Meanwhile, in the social practice dimension, Antaranews.com coverage demonstrates how the media shape public understanding regarding the global position of the Indonesian language.